“I am a Lonely Bird:”: Psalm 102 and the Psychology of Loneliness - Hildebrandt, Samuel (Biblical theology bulletin, 2023)
Already an urgent issue before the Covid-19 pandemic, the reality of loneliness became plain to see especially during the lockdowns and social protocols of those years. What we understand about this social phenomenon, however, is often as vague as the biblical assessment that lonely living is “not good” (Genesis 2:18). My study expands and explains what the Bible has to say on the topic (1) by identifying other relevant texts about loneliness, (2) by studying the imagery of the “lonely bird” in Psalm 102, and (3) by bringing these insights into conversation with contemporary psychological research. Their differences notwithstanding, I will show that the ancient psalm and modern psychology join their voices in portraying loneliness as a liminal and lethal force. Inasmuch as the struggle of articulation and acknowledgement hinders many from seeking support, the first-person poetry of the “lonely bird” in Psalm 102 can give language to human experience, break false assumptions, provide companionship, and pave the way towards a new-found freedom.